A STUDY ON POSITIVE SELF-ACCEPTANCE IN STUDENTS EXPERIENCING FATHERLESSNESS - Desinta, Evit; Setiawati, Denok; Nursalim, Mochamad; Ghozali, Muhamad Afifuddin (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study explores the process of positive self-acceptance among fatherless adolescents in Indonesia, a phenomenon that remains underexamined within the cultural and educational context. The research aims to understand how emotional regulation, coping strategies, and social support contribute to adolescents’ self-acceptance after experiencing the absence of a father due to death, divorce, or lack of involvement. Using a qualitative phenomenological design, data were collected through in-depth interviews with five students aged 15–18 from SMA Negeri 2 Purbalingga, along with guidance and counseling teachers as triangulation sources.The results reveal that self-acceptance among fatherless adolescents is a dynamic and contextual process characterized by four patterns: stable, fluctuating, struggling, and transformative. Emotional awareness, gratitude, and social relationships particularly maternal support and counselor involvement emerged as crucial factors in fostering resilience. These findings highlight that father absence does not always lead to maladjustment; instead, it may serve as a pathway for personal growth and emotional maturity when supported by relational and communal resources. This study contributes to the understanding of adolescent well-being within a collectivist culture and provides practical implications for school-based counseling programs emphasizing emotional literacy, self-compassion, and social connectedness.